2018
DOI: 10.1097/01.blo.0000533629.49193.09
|View full text |Cite|
|
Sign up to set email alerts
|

The 2018 Otto Aufranc Award: How Does Genome-wide Variation Affect Osteolysis Risk After THA?

Abstract: Background Periprosthetic osteolysis resulting in aseptic loosening is a leading cause of THA revision. Individuals vary in their susceptibility to osteolysis and heritable factors may contribute to this variation. However, the overall contribution that such variation makes to osteolysis risk is unknown. Questions/purposes We conducted two genome-wide association studies to (1) identify genetic risk loci associated with susceptibility to osteolysis; and (2) identify genetic risk loci associated with time to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(46 reference statements)
0
12
0
1
Order By: Relevance
“…891 British Caucasian men and women (481 controls and 410 cases) who had previously undergone hip replacement for idiopathic osteoarthritis were studied. 59 Controls comprised subjects who had no evidence of HO on plain AP radiographs of the pelvis taken not less than 1 year following primary THA. Cases comprised subjects with radiographic evidence of post-operative HO and were graded (0-4) using the Brooker classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…891 British Caucasian men and women (481 controls and 410 cases) who had previously undergone hip replacement for idiopathic osteoarthritis were studied. 59 Controls comprised subjects who had no evidence of HO on plain AP radiographs of the pelvis taken not less than 1 year following primary THA. Cases comprised subjects with radiographic evidence of post-operative HO and were graded (0-4) using the Brooker classification.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria have been previously described. 59,61 Briefly, individuals with 1) gender discrepancy; 2) call rate <95% (<97% in arcOGEN 61 ); 3) excess homozygosity or heterozygosity (more than ±3 SD of the mean); 4) duplicates and related samples (π^ >0.2); 5) non-UK European ancestry (ethnicity outliers) were excluded from further analyses. Variants with 1) minor allele frequency (MAF) ≥5% and a call rate <95%, or a MAF <5% and call rate <99%; 2) monomorphic; 3) exact Hardy Weinberg Equilibrium (HWE) p<0.05 (p<0.0001 in arcOGEN) were also excluded from the merged dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Several genetic variations of single-nucleotide polymorphisms (SNPs) are associated with an increased risk of aseptic loosening, as follows: IFIT2/IFIT3 (odds ratio = 21.6), CERK (odds ratio = 12.6) and PAPPA (odds ratio = 14) [45]. Another study supports the importance of genome impact on osteolysis susceptibility [46]. A systematic review performed by Del Buono et al showed overexpression of the following genes in the cases of aseptic loosening: TNF-238 A allele, IL6-174 G allele, interleukin (IL)-6 (-597) and (-572), TNF-alfa promoter (-308G-A), and MMP-1 promoting gene [47].…”
Section: Geneticsmentioning
confidence: 88%
“…The GWAS cohort comprised 194 men and 216 women of UK European ancestry, mean age (±standard deviation) 63.4 ± 8.9 years, who had previously undergone hip replacement for idiopathic osteoarthritis and were genotyped as previously described [ 60 ]. Patients with a history of inflammatory arthritis, secondary arthritis due to trauma, avascular necrosis, developmental and childhood hip disorders, and subjects who had taken immuno-suppressant agents or bisphosphonates for a continuous period of greater than 6 months since primary THA were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Standard GWAS quality control (QC) was conducted at the sample and variant levels and exclusions applied, as previously described [ 60 , 62 ]. Following QC, 410 subjects and 448,770 variants were imputed with IMPUTE2 [ 63 ] using the European reference panel (1000 Genomes Project, Dec 2010 phase I interim release) [ 64 ].…”
Section: Methodsmentioning
confidence: 99%